Distributed Ledger Technologies and Corruption: The Killer App? - Marks, Jesse (Science and Technology Law Review, 2019)
As futurists continue to speculate about DLTs’ seemingly limitless potential, and as pilots begin on a range of potential applications of the technology to anti-corruption efforts, this Article contextualizes these developments and considers DLTs’ big-picture implications. This Article proceeds in five parts. Part II provides a brief background on DLTs: what they are, what they do, and where they originate. Part III positions this discussion within the broader anti-corruption literature and offers a framework for government officials, aid agencies, and reformers considering whether to deploy new technologies in the fight against corruption. Applying that framework to DLTs, Part IV identifies three anti-corruption use cases for which governments should particularly consider DLTs. Part IV also examines some of the key risks in using blockchains to fight corruption and outlines strategies governments can use to mitigate those risks. Part V recommends some short- and long-term steps for governments interested in exploring DLTs. Part VI concludes with a note of caution about the rapidly evolving nature of these technologies.